Analysis of the ECH effect on EPM/AE stability in Heliotron J plasma using a Landau closure model. (28th December 2022) - Varela, J.; Nagasaki, K.; Kobayashi, S.; Nagaoka, K.; Adulsiriswad, P.; Cappa, A.; Yamamoto, S.; Watanabe, K.Y.; Spong, D.A.; Garcia, L.; Ghai, Y.; Ortiz, J.
Abstract: The aim of the present study is to analyze the effect of the electron cyclotron heating (ECH) on the linear stability of Alfvén eigenmodes (AEs) and energetic particle modes (EPMs) triggered by energetic ions in Heliotron J plasma. The analysis is performed using the FAR3d code that solves a reduced MHD model to describe the thermal plasma coupled with a gyrofluid model for the energetic particle (EP) species. The simulations reproduce the AE/EPM stability trends observed in the experiments as the electron temperature ( T e ) increases, modifying the thermal plasma β, EP β and EP slowing-down time. Particularly, the n / m = 1 / 2 EPM and 2 / 4 Global AE are stabilized in the low-bumpiness (LB) configuration due to an enhancement of the continuum, finite Larmor radius and e-i Landau damping effects as the thermal β increases. On the other hand, a larger ECH injection power cannot stabilize the AE/EPM in medium-bumpiness and high-bumpiness (HB) configurations because the damping effects are weaker compared to the LB case, unable to balance the further destabilization induced by an enhanced EP resonance as the EP slowing-down time and EP β increases with T e .